“I Did Not Want to Make a Bigger Deal Out of It than It Was”: A Mixed-Method Study on the Help-Seeking Behavior of Victims of Image-Based Sexual Harassment and Abuse - Pijlman, Valérie (Journal of interpersonal violence, 2025)
Experiencing image-based sexual harassment and abuse (IBSHA), or the sending of unsolicited nude or sexual images and the nonconsensual taking, sharing, or threats to share nude or sexual images, may have severe consequences for victims’ well-being. While seeking help may be beneficial, not every victim seeks help. Little research has been conducted on IBSHA victims’ help-seeking behavior. Therefore, the present mixed-method study examined the help-seeking behavior of IBSHA victims, particularly the barriers and facilitators to seeking help. The study used data from an online survey (N = 163) and interviews (N = 6) among 12-to-25-year-old victims. The quantitative data indicated that the majority of victims disclosed the incident (72.8%), but only a third received help (34.4%). Help-seekers reported greater experienced barriers to help-seeking, when compared to non-help-seekers. The experienced barriers positively predicted victims’ reported help-seeking behavior. From the qualitative data, four types of barriers were identified: (a) individual barriers (e.g., feelings of shame), (b) practical barriers (e.g., affordability of help), (c) interpersonal barriers (e.g., fear of negative reactions from one’s social environment), and (d) sociocultural barriers (e.g., normalization of IBSHA). Moreover, two types of facilitators were identified: (a) individual facilitators (e.g., the impact of victimization) and (b) interpersonal facilitators (e.g., social support). This suggests victims experience multiple barriers, which altogether can influence their help-seeking behavior. As a help-seeking trajectory is complex and unique to the individual, victims may encounter multiple new hurdles along the way. This may explain why help-seekers reported more barriers. The findings and corresponding implications highlight the importance of providing education on IBSHA and help-seeking on various levels in society.